2002
DOI: 10.1021/ol027056d
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Stability of Helical Peptides Containing a Thioamide Linkage

Abstract: [structure: see text] Thioxo peptide analogues of the alpha-helical peptide GCN4-p1 were synthesized and evaluated for helicity and oligomeric state. Sedimentation equilibrium and CD measurements indicate that the thioxo peptides fold into parallel alpha-helical coiled coil structures essentially identical to the native structure. This work marks the first incorporation of a thioamide linkage into the backbone of an alpha-helix and demonstrates that a thioamide linkage is compatible with positions within the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
75
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 19 publications
0
75
0
Order By: Relevance
“…Miwa and co-workers have demonstrated the possibility of incorporating thioamide linkages in b sheet and a helix secondary structures. [15,16] A b sheet structure adopted by a thiopeptide is very similar to that of the corresponding oxopeptide, while a single thio substitution even increases the thermal stability of an a helix. This is due to stronger acidity of the thioamide hydrogen, as a consequence of the longer C= S bond and the lower electronegativity of sulfur.…”
Section: Introductionmentioning
confidence: 98%
“…Miwa and co-workers have demonstrated the possibility of incorporating thioamide linkages in b sheet and a helix secondary structures. [15,16] A b sheet structure adopted by a thiopeptide is very similar to that of the corresponding oxopeptide, while a single thio substitution even increases the thermal stability of an a helix. This is due to stronger acidity of the thioamide hydrogen, as a consequence of the longer C= S bond and the lower electronegativity of sulfur.…”
Section: Introductionmentioning
confidence: 98%
“…Thioxo-peptide bonds slightly restrict conformational space of the polypeptide backbone (16)(17)(18) but are tolerated in α-helices and β-sheets (19)(20)(21). Thioxylation destabilizes α-helices by about 7 kJ∕mol relative to an oxo-amide bond (21), which makes thioxo-peptide bonds a perfect tool to monitor formation of individual backbone hydrogen bonds during protein folding reactions.…”
mentioning
confidence: 99%
“…This wavelength is easily accessible for femtosecond lasers (since it is obtained by tripling the Ti:S laser wavelength), and S-O substitution may be done site-selectively. Furthermore, it has been shown that incorporation of a thioamide linkage results in only minor changes of the secondary structure of a peptide [83,84] and that secondary structure is indeed changing upon illumination of thiopeptides [85,86]. A recent combined theoretical-experimental femtosecond studies on the photoswitch itself (CH 3 -CSNH-CH 3 ) shows that the isomerization quantum yield is high (30-40%), that the molecule is stable against photodegeneration, and that the isomerization proceeds through two reaction channels, one ultrafast with a <5 ps time constant and one slower with a 200 ps time constant [87].…”
Section: Vibrational Spectroscopy Of Non-equilibrium Dynamics Of Peptmentioning
confidence: 99%